Race, class, and the death penalty: capital punishment in American history - Allen, Howard W. (State University of New York Press, 2008)
The death penalty in national perspective -- The colonial and revolutionary era -- The early republic, 1786-1865 -- The south and the border, 1866-1945 -- The northeast, 1866-1945 -- The western regions, 1836-1945 -- Social perspectives -- The death penalty after 1945 -- The death penalty in American history